"Ha'azinu" (Deut 32, 1-43): Structure and Significance. Issue 1 (2nd January 2021) - Sklarz, Miriam
ABSTRACT: Various divisions of the Song of Haazinu (Deut 32:1-43) have been proposed, based on diverse considerations of theme, meter, and language. The suggested division criteria, however, were not consistent and unequivocal throughout all the parts of the structure, and the various proposals did not gain a wide consensus. This article proposes a new division that reveals a symmetrical structure that is based on recurring and synonymous wordings in the Song and that highlights the Song's ideational meaning.